Communication and geography: narratives about the study in the Meruri Village of the Bóe-Bororo indigenous people: For a communication of (re)cognition: dialogical encounters in Boe-Bororo territory (Élisée - Revista de Geografia da UEG, 2025)
Considering the Humanist Geography that recognizes local narratives and the representativeness of experiences, historical origins related to places and also values ​​narratives that reveal traditions, memories and subjectivity, this work used autoethnographic reporting as a methodological resource and praxis.  We sought to support self-reflexive texts based on theories and thinkers from Geography, Autoethnography and Communication, to “put in common” realities that were less explored by traditional/conservative scientific production. This work intends to do justice to the proposals of the Master's in Geography and the Communication and Geography discipline, also expressing as fully and deeply the perceptions about the space of Aldeia Meruri, of the Boe Bororo indigenous people.
Keywords: Comunicación, autoetnografía, lugar, pueblos originarios.